Edad y crecimiento en Bufo arenarum (Anura: bufonidae) - Filipello, Ana María (1990)
A sample of 88 (45 frmale and 43 nales) adults and subadults toads of Bufo arenarum has been collected in Buenos Aires province, Argentina. There has been studied the age and increments in growth by the squeletochronological method in the subdistal phalange of the third finger from the hand. Statistical regression analysis (linear and power models) were perfomed. These studys showed that: a) snowt-vent (total lenght, LT=y) and head width (AC=y) have a strong positive correlation to the estimate age (number of LAC present in the bone; E=x). The power model shows the best fitting to the female data and the linear model provide good fits to the male data. All correlation coefficients are statistically significant at 0,01 probability level. b) The equation of von Bertalanffy was fitted to the data (LT; AC): Males growth showed a weak fitting to von Bertalanffy. Female corporal growth (LT and AC) showed the best fitting to von Bertalanffy equation. It can be used 90-110 mm as the length at sexual maturity (or sexual maturity size). c) The endosteal resorption begings before males rearch the sexual maturuty (E IV). In the females the endosteal resorption starts after the sexual maturity (E V). d) The third LAC could be compleyely resorbed at E VI.